Effective management of peripheral vertigo in the real-world setting: an expert survey with neurologists in India - Chako, Fiju; Gnanashanmugham (International Journal of Research in Medical Sciences, 2026)
Background: Benign paroxysmal positional vertigo (BPPV) accounts for approximately 20% of all cases of vertigo. Despite successful repositioning maneuvers, a significant proportion of patients experience residual dizziness, characterized by a persistent sensation of imbalance without true vertigo. The Epley maneuver remains the standard treatment for BPPV; however, adjunctive therapy with betahistine has been shown to facilitate vestibular compensation, thereby reducing residual dizziness and the risk of recurrent vertigo. This study aimed to assess expert opinions on the role of betahistine 48 mg/day for 3 months in preventing vertigo recurrence and reducing residual dizziness in patients with BPPV in real-world clinical practice. Methods: Total 43 neurologists from diverse regions across India treating BPPV participated in the survey. A literature review based on the Medline database search was used to prepare a structured questionnaire about BPPV management, treatment practices, recurrence, and residual dizziness. Results: Among the surveyed experts, 37% reported vertigo recurrence in 10-25% of patients following repositioning maneuvers. A majority (56%) indicated routine prescribing of betahistine at 48 mg/day. Furthermore, 67% opined that improved vestibular compensation and enhanced vestibular blood supply contributed to reduced recurrence, while 68% acknowledged the dose-dependent efficacy of betahistine. Notably, 35% reported a 75-90% reduction in residual dizziness with betahistine 48 mg/day administered for 3 months. Conclusions: Residual dizziness and recurrence remain common after successful repositioning maneuvers in BPPV. Expert opinion from real‑world practice supports adjunctive treatment with betahistine 48 mg/day for at least 3 months to facilitate vestibular compensation and significantly reduce residual dizziness and recurrence, with a favorable safety profile.